Effectiveness and Safety of Rituximab in Recalcitrant Pemphigoid Diseases - Lamberts, Aniek; Euverman, H. Ilona; Terra, Jorrit B.; Jonkman, Marcel F.; Horváth, Barbara (Frontiers in Immunology, 2018)
Introduction: Rituximab (RTX) is a monoclonal antibody targeting CD20, a transmembrane protein expressed on B cells, causing B cell depletion. RTX has shown great efficacy in studies of pemphigus vulgaris, but data of pemphigoid diseases are limited. Objective: To assess the effectiveness and safety of RTX in pemphigoid diseases. Methods: The medical records of 28 patients with pemphigoid diseases that were treated with RTX were reviewed retrospectively. Early and late endpoints, defined according to international consensus, were disease control (DC), partial remission (PR), complete remission (CR) and relapses. Safety was measured by reported adverse events. Results: Patients with bullous pemphigoid (BP; n=8), mucous membrane pemphigoid (MMP; n=14), epidermolysis bullosa acquisita (EBA; n=5) and linear IgA disease (LAD; n=1) were included. Treatment with 500mg RTX (n=6) or 1000mg RTX (n=22) was administered on day 1 and 15. Eight patients received additional 500mg RTX at month 6 and 12. Overall, DC was achieved in 67.9%, PR in 57.1%, and CR in 21.4% of the cases. During follow-up 66.7% patients relapsed. Repeated treatment with RTX led to remission (PR or CR) in 85.7% of the retreated cases. No significant difference in response between pemphigoid subtypes was found. IgA-dominant cases (n=5) achieved less DC (20% vs. 81.3%; p=0.007), less PR (20% vs. 62.5%; p=0.149) and less CR (0% vs. 18.8%; p =0.549) compared to IgG-dominant cases (n=16). Five severe adverse events and three deaths were reported. One death was possibly related to RTX and one death was disease related. Conclusion: RTX can be effective in recalcitrant IgG-dominant pemphigoid diseases, however not in those where IgA is dominant.